Reducing the negative appendectomy rate with the laparoscopic appendicitis score; a multicenter prospective cohort and validation study. (July 2020) - Gelpke, Koen; Hamminga, Jenneke T.H.; van Bastelaar, James J.; de Vos, Bart; Bodegom, Maarten E.; Heineman, Erik; Hofker, H. Sijbrand; El Moumni, Mostafa; Haveman, Jan Willem
Abstract: Background: Approximately nine percent of all acute appendectomies are unintentionally performed on a normal appendix. Failure of treatment (negative appendectomy or missed appendicitis) is associated with higher morbidity and mortality when compared to appendectomy for uncomplicated appendicitis. The Laparoscopic APPendicitis (LAPP) score was developed in order to systematically evaluate the appendix for the presence of inflammation. This study aims to determine whether the LAPP score reduces the negative appendectomy rate without missing appendicitis. Methods: From September 2013 through May 2016, 322 adult patients presenting with a clinical suspicion of acute appendicitis and an indication for diagnostic laparoscopy were included and analyzed in this multicenter prospective validation study. Depending on the LAPP score, the appendix was either removed (n = 300) or left in situ (n = 22). These patients were compared to a historical control group of 584 patients treated at the same hospitals. The appendix was examined by a pathologist and the negative appendectomy rate was calculated. Results: The negative appendectomy rate was significantly lower when the LAPP score was used (4, 7% vs. 8, 4%; P = 0, 034). None of the patients with a negative LAPP score, in which the appendix remained in situ, developed acute appendicitis within three months. There were no significant differences in operation time, complications, or readmissions. Using the LAPP score was associated with significantly higher rates of preoperative radiological imaging (98% vs. 70%; P < 0, 001). After adjusting for covariables, including radiological imaging, use of the LAPP score led to fewer treatment failures when compared to not using the LAPP score (OR: 0, 48, 95% C.I. 0, 251 to 0, 914; P = 0, 025). Conclusion: The LAPP score is a safe and simple tool to reduce the negative appendectomy rate during laparoscopic surgery without missing cases of acute appendicitis. Highlights: Negative appendectomy occurs at a rate of 9% after laparoscopic surgery for suspected appendicitis. An appendectomy of a non-inflamed appendix has its morbidity. Removing normal looking appendix is unnecessary, even in absence of other pathology. Laparoscopic appendicitis score is useful for evaluation of the appendix for presence of inflammation. Laparoscopic appendicitis score reduces negative appendectomy rate without missing appendicitis.